Village Midline Study: Rupandehi, Nepal - Bhusal, Aastha; Pudasaini, Roshan; Paras, B.K.; Nagpal, Mansi; Khatri-Chhetri, Arun (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This report presents the findings from the village midline study conducted in Madhuri Village, the CCAFS benchmark site of Rupandehi district, Nepal between the 26th and the 30th of May 2019 . This document reports on the various changes which have occurred since the baseline was conducted in the same village. Changes in agricultural practices, sources of information, organizational and institutional development, climate change adaptation practices, and networks present in the community are assessed. During the village midline study, the participants identified 16 different organizations working closely with the community. These organizations provide support to households in the village in sectors such as agriculture, livestock, finance, saving and credits, infrastructural development, or irrigation. Special attention was paid to organizations which were working on food security and natural resource management. There have been significant changes in the federal government structure which has provided opportunities for the villagers. Women-led cooperatives were instrumental in uplifting the status of women and empowering them economically. Very few organizations working in the sector of natural resource management were cited by participants. Both groups identified that the information on seed selection and spacing, timing of fertilizers application along with information on irrigation have been received from cooperatives and agro-vets. Relatives and rural municipality played an important role in disseminating the information in the village. However, the frequency at which information was being spread was noted to be very low. Training on climate change and climate change adaptation, sustainable development, natural resource conservation and management, need to be the focus of future activities. Proper linkages and coordination mechanisms between both governmental and non –governmental organizations are necessary for the community to combat climate change’s negative impacts and increase resilience within the village.